Controle da gestão pública e participação cidadã: a experiência da ouvidoria do Tribunal de Contas de Pernambuco - Barreto, Waléria da Cruz Sá (2009)
Amongst numerous topics of social interest, this research has focused on the relationship between the state and society, highlighting the role of administrative improbity control as a relevant instrument for improving public management, as well as the living conditions of the general population. The research also emphasizes the role of the Tribunal of Accounts of the State of Pernambuco, the manners in which institutional control is achieved and the way that citizens are able to exercise social control over government authorities. The results of the studies, based on an overview of the literature regarding the subject, together with the experience of the Tribunal of Accounts, not only indicate ways that lead towards social participation, but also the need for constant reflection concerning institutional practices. The research has understood the identification of the communication channels established between the Tribunal of Accounts in Pernambuco and society, through the programs of the Professor Barreto Guimarães School of Public Accounts and, especially, the Ombudsman. The work has also outlined the document provided by the Tribunal, regarding reports of irregularities originating from members of the public. An analysis of the irregularities and the repercussions of the participation of members of the public were observed during the trials that originated from demands by the Ombudsman. The study also offers an overview of the organization and workings of the Tribunal of Accounts in the State of Pernambuco, as well as its relationship with society, while searching for a more effective control of administrative improbity. Considering the innovative nature of investigations within the area of activities within the Tribunal of Accounts, the approach employed by this study has been of an exploratory nature.